Climate Change And Campus Sustainability Volume I - Awangku Hassanal Bahar Pengiran Bagul; Jainurin Justine; Andy Lee Chen Hiung; Mohd Rizwan Abd Majid; Andi Tamsang Andi Kele; Datu Razali Datuk (Datu) Eranza; Lau Hui Keng; Mohd Allif Anwar bin Abu Bakar; Rostika Petrus Boroh; Tini Maizura Mohtar (Penerbit UMS, 2018)
Climate Change And Campus Sustainability Volume I (Selection of papers presented at the 5th Regional Conference on Campus Sustainability 2018 (5RCCS2018))